Prevalence and intensity of gastrointestinal nematode infection in domestic horses (Equus Caballus) in the Sudano-Guinean Altitude Zone of the North West Region of Cameroon - mbafor, fidelia lem (European Journal of Applied Sciences, 2021)
A study was conducted from March to September 2020 in five Sub-Divisions in Donga Mantung to determine the prevalence and intensity of gastrointestinal (GI) nematode infection of domestic horses with the objective to develop and implement strategic parasitic control measures. A total of 794 randomly selected horses (317 males and 477 females), aged ≤1 to ≥7 years old were examined using standard parasitological procedure. Fresh fecal samples were collected from the rectum and examined coprologicaly in the laboratory for the presence of GI nematode eggs. A qualitative flotation technic using saturated sodium chloride solution and a quantitative technic using the Mc Master Slide method of coprological analysis were realized. Result indicated nine species of nematodes (Strongylus equinus, Parascaris equorum, Oxyuris equi, Habronema muscae, Strongyloides westeri, Trichostrongylus axei, Trichonema sp, Triodontophorus serratus and Dictyocaulus aenfieldi) were identified. Horses harbored one or more nematode infection with a total prevalence rate of 100% for the gastrointestinal nematodes. The two genera of nematodes commonly encounter during the study period were Strongylus equinus type of egg (97,0% ) and Parascaris equorum (52,0%) in horses. There was a significant difference (P<0.05) in prevalence of Strongyle type of eggs and P. equorum between species. The mean intensity of infection was 1459 ± 956 in horses with age 3 years. Poly-parasitic infections with prevalence of 98,0% were more common than mono-parasitic infections of 2,0%. These results suggest the possible need of studying the epidemiology, economic impact of these nematodes affecting the equine industry, stimulating important aspects to livestock programs and prevention activities.